The Architecture Of Fortifications In Ancient Syria (Damascus University Journal of Historical Studies, 2023)
Walls and fortifications appeared in architecture during the Chalcolithic period as evidence in urban architecture. Some types of fortifications appeared before this date, and these fortifications appeared in Jericho and Tal Al Sawan. But this architecture did not give a permanent character to this era. The procession of cities was linked to the presence of fortifications as a basis in their architecture (HamoKar, Tel Brak, Habouba and others). In addition, inside the city there were fortifications, in the area of ​​the palace and the temple, where they were fortified and isolated from the low area. And there are earthen berms at high heights separated by distances from the wall whose foundations are made of stones and then developed with the development of city plans from circular shape to polygonal shape, especially with the beginning of 2000 BC. With the exception of the city of Mari, which has preserved its circular shape.
Keywords: walls; fortifications; earth mounds; towers; defensive system